Could new information influence attitudes to foods supplemented with edible insects?. Issue 9 (4th September 2017) - Barsics, Fanny; Caparros Megido, Rudy; Brostaux, Yves; Barsics, Catherine; Blecker, Christophe; Haubruge, Eric; Francis, Frédéric
Abstract : Purpose: Broader acceptance of entomophagy (i.e. human consumption of insects) will depend on factors that impact consumers' perceptions of edible insects. The purpose of this paper is to examine how a broad-based information session would affect consumers' perceptions and attitudes about an edible insect product. Design/methodology/approach: During a taste testing session, preceded or followed by an information session about entomophagy, participants rated the organoleptic characteristics of two bread samples on nine-point hedonic scales. The two bread samples were identical, though one was faux-labelled as containing an insect product. Findings: Generalised linear model (GLM) analysis showed effects of gender, information session exposure, entomophagy familiarity, and entomophagy experience on participants' ratings of the samples. Wilcoxon-Mann-Whitney ranked sum tests showed that appearance, flavour, and overall liking were significantly better rated for the bread sample labelled as insect free by participants who attended the presentation a priori. Potential ways to improve information content and delivery in favour of encouraging dietary shifts are discussed. Practical implications: This study shows that information about insect-based products could change consumers' perceptions of such products. The results provide clues regarding how the food industry can adapt communication for target audiences. Originality/value: Actual edible insect products were not used in this study. Paradoxically, it is the first to show the impact of an information session on the acceptability of edible insect products, by revealing participants' perceptual expectations.